2020
DOI: 10.3390/ijms21155296
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor Beta/Delta Agonist Suppresses Inflammation and Promotes Neovascularization

Abstract: The effects of peroxisome proliferator-activated receptor (PPAR)β/δ ophthalmic solution were investigated in a rat corneal alkali burn model. After alkali injury, GW501516 (PPARβ/δ agonist) or vehicle ophthalmic solution was topically instilled onto the rat’s cornea twice a day until day 7. Pathological findings were evaluated, and real-time reverse transcription polymerase chain reaction was performed. GW501516 strongly suppressed infiltration of neutrophils and pan-macrophages, and reduced the mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…I-κBα inhibits NF-kB nuclear translocation and restricts transcription downstream of the NF-κB signaling pathway [24]. Previous studies have reported that PPARα and PPARβ/δ suppress NF-κB [9,11,14]. In the present research, immunostaining and cell counting analyses showed that all PPAR subtypes suppressed NF-κB expression.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…I-κBα inhibits NF-kB nuclear translocation and restricts transcription downstream of the NF-κB signaling pathway [24]. Previous studies have reported that PPARα and PPARβ/δ suppress NF-κB [9,11,14]. In the present research, immunostaining and cell counting analyses showed that all PPAR subtypes suppressed NF-κB expression.…”
Section: Discussionsupporting
confidence: 58%
“…In ophthalmology, PPARs have recently been reported to affect inflammation, fibrosis, and angiogenesis [13,14,18,19]. However, there are few reports of the effects of PPARs on corneal epithelial wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with LPS-induced M1 macrophage culture supernatant stimulated the osteoclastogenesis (Zhang et al, 2021). PPARβ/δ agonist has been found to reduce the expression of inflammatory factors such as IL-1β and IL-6 by inhibiting NF-κB signaling (Rival et al, 2002;Bishop-Bailey and Bystrom, 2009;Coll et al, 2010), and promote the recruitment of M2 macrophages to accelerate the injury repair process (Tobita et al, 2020). However, its role in diabetic osteoporosis has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of PPAR expression in ocular and periocular tissues has been described to be linked to the regulation of the local immune-inflammatory, fibrogenic and neo-angiogenic process [ 57 ].…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%